A miniprep procedure for isolating genomic DNA from Magnoporthe grisea - J. A. SWEIGARD; M. J. ORBACH; B. VALENT; F. G. CHUMLEY (Fungal Genetics Reports, 1990)
We have developed a simple miniprep procedure for the isolation of genomic DNA from the ascomycete Magnaporthe grisea. This pathogen of many grasses, including rice, has a moderate growth rate and produces intermediate to low numbers of conidia when grown in culture. Thus, in our previous DNA preparation procedure we inoculated swirling liquid cultures with mycelium that had been fragmented in a blender rather than with conidia. The mycelium obtained from these cultures was ground in liquid nitrogen for DNA extraction. Though the quantity and quality of DNA obtained by this method is satisfactory, the technique is too laborious for analysis of many strains. We developed the procedure described below to eliminate the need to fragment mycelium in a blender to inoculate cultures and to eliminate the need to grind mycelium in liquid nitrogen for DNA extraction. The new procedure, which relies on the enzymatic removal of cell walls and the lysis of protoplasts, should be readily adaptable to other filamentous fungi with growth characteristics similar to those of M. grisea.